Pemanfaatan Aplikasi Pembelajaran Bahasa Inggris Duolingo dan Busuu Menggunakan Media Smartphone - Pale, Erlinda Sonya; Luruk, Fransiska Densiana; Sulaiman, Eugelin; Banfoe, Petrus (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2024)
The current community service aims at socializing and introducing how Duolingo and Busuu applications were used in English learning. This activity was undertaken in a Junior High School at the border area between Indonesia and Timor Leste, SMPN Napan grade IXA. The problem to be addressed in this activity was the absence on the use of English applications to support the learning. This fact was supported by observation result in which the English learning focus only on the use of some textbooks. The method comprises 3 stages: informing how to operate Duolingo and Busuu applications to the students, executing the English learning process supported by Duolingo and Busuu applications, and checking the students’ understanding on the use of both applications. The outcome of the community service pinpointed that the students were very enthusiastic when they operated those applications. Moreover, the interesting design of those applications encouraged the students to complete exercises in the applications. The class atmosphere was becoming more alive even though the learning process was done at noon or in the afternoon.